Quality of basic health care and social vulnerability: a spatial analysis - Katyucia Oliveira Crispim de Souza; Lislaine Aparecida Fracolli; Caíque Jordan Nunes Ribeiro; Andreia Freire de Menezes; Glebson Moura Silva; Allan Dantas dos Santos (SciELO, 2021)
ABSTRACT Objective: To analyze the association between quality of basic health care and social vulnerability in municipalities of the Brazilian northeast. Method: Ecological study with spatial analysis using univariate global and local Moran's indexes. Bivariate analyses were employed to examine the relationship between the quality of basic health care and the Social Vulnerability Index in the Northeast. The dependent variable corresponded to the final scores of certifications of teams of basic health care in the Northeast that had participated in the third cycle of the Brazilian Program for the Improvement of Access and Quality of Basic Health Care. The independent variable was the Social Vulnerability Index of the municipality. Results: The bivariate analysis has pointed out the presence of areas of low vulnerability with high quality basic health care in the municipalities in the states of Piauí, Ceará, Rio Grande do Norte, Pernambuco, and Bahia. The state of Maranhão is emphasized for its low performance in basic health care in a large number of municipalities with high vulnerability. Conclusion: The study has revealed a spatial relation between the indicators of social vulnerability and quality of basic health care in the Northeast, suggesting that limitations in access to health resources and services may be related to social and health determinants.